2021
DOI: 10.3389/fonc.2021.638360
|View full text |Cite
|
Sign up to set email alerts
|

Targeting KRAS: The Elephant in the Room of Epithelial Cancers

Abstract: Mutations of the proto-oncogene KRAS are the most frequent gain-of-function alterations found in cancer. KRAS is mutated in about 30% of all human tumors, but it could reach more than 90% in certain cancer types such as pancreatic adenocarcinoma. Although historically considered to be undruggable, a particular KRAS mutation, the G12C variant, has recently emerged as an actionable alteration especially in non-small cell lung cancer (NSCLC). KRASG12C and pan-KRAS inhibitors are being tested in clinical trials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 150 publications
1
28
0
Order By: Relevance
“…An important feature of KRAS mutant tumors is the immunosuppressive state ( 40 ). KRAS signaling induces the expression of immune regulatory factors and inflammatory cytokines in tumor cells, and subsequently recruits neutrophils and myeloid-derived suppressor cells (MDSC) to form an immunosuppressive tumor microenvironment ( 41 ). Mutated KRAS in pancreatic cancer plays a central role in tumor development and growth by regulating T-cell cytokines in TME.…”
Section: Discussionmentioning
confidence: 99%
“…An important feature of KRAS mutant tumors is the immunosuppressive state ( 40 ). KRAS signaling induces the expression of immune regulatory factors and inflammatory cytokines in tumor cells, and subsequently recruits neutrophils and myeloid-derived suppressor cells (MDSC) to form an immunosuppressive tumor microenvironment ( 41 ). Mutated KRAS in pancreatic cancer plays a central role in tumor development and growth by regulating T-cell cytokines in TME.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunosuppression in the TME is related to mutations in KRAS. A related study [31] showed that mutations in the TP53 gene are common in tumours and affect the recruitment and activity of T cells, thus also leading to immune evasion [32] . These m6A-associated lncRNA gene mutations are closely associated with immune activity in the TME, suggesting an interaction between m6A modi cations and tumour immunogenomics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, germline BRCA mutations have been validated as a predictive factor of response to the PARP inhibitor olaparib after platinum-based chemotherapy in the metastatic setting [85]. Other therapeutic targets that are being investigated in advanced disease include homologous recombination repair deficiency (HRD), microsatellite instability, HER2/HER3, CDK4/6, NTRK fusions, KRAS G12C, and BRAF mutations [83,86,87].…”
Section: Novel Molecular Targets and Possible Implications For Treatment Of Early-stage Pancreatic Cancermentioning
confidence: 99%